2014
DOI: 10.1088/1741-2560/11/2/026011
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling of an endovascular approach to deep brain stimulation

Abstract: Together, these results suggest that endovascular DBS can serve as a complementary approach to stereotactic DBS in select cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 92 publications
1
38
0
Order By: Relevance
“…Electrodes positioned temporarily within intracranial vessels enabled recording of both spontaneous and evoked EEG-like electrical activity (Driller et al, 1969), and this work was recently extended to multi-electrode recordings using a chronically implanted stent-like device (Oxley et al, 2016). Stimulation through the blood vessel wall is also possible, an example being endovascular stimulation of the vagus nerve (Nabutovsky et al, 2007), and a recent simulation analysis demonstrated comparable patterns of model nerve fiber activation between an intravascular electrode and traditional stereotactically-positioned DBS leads (Teplitzky et al, 2014). This is not to suggest that intravascular methods are without risk; however, such innovations may provide a less-invasive approach to both record and stimulate deep in the brain and thus, represent new way to deliver DBS.…”
Section: Development In Technology and Applicationmentioning
confidence: 99%
“…Electrodes positioned temporarily within intracranial vessels enabled recording of both spontaneous and evoked EEG-like electrical activity (Driller et al, 1969), and this work was recently extended to multi-electrode recordings using a chronically implanted stent-like device (Oxley et al, 2016). Stimulation through the blood vessel wall is also possible, an example being endovascular stimulation of the vagus nerve (Nabutovsky et al, 2007), and a recent simulation analysis demonstrated comparable patterns of model nerve fiber activation between an intravascular electrode and traditional stereotactically-positioned DBS leads (Teplitzky et al, 2014). This is not to suggest that intravascular methods are without risk; however, such innovations may provide a less-invasive approach to both record and stimulate deep in the brain and thus, represent new way to deliver DBS.…”
Section: Development In Technology and Applicationmentioning
confidence: 99%
“…Teplitzky et al also demonstrated that with a unilateral electrode implant, endovascular DBS was superior to stereotactic DBS in the production of contralateral activation and comparable to stereotactic DBS in neuronal activation. 31 Further investigation into the stimulation parameters (such as the current levels) and the safety profile of intravascular stimulation is necessary.…”
Section: Deep Brain Stimulationmentioning
confidence: 99%
“…Endovascular EEG could be used in the preoperative evaluation of patients for epilepsy surgery, 5,16,19,22 or even in the determination of resection margins that could possibly be treated endovascularly. 2 In addition, computational modeling has demonstrated the feasibility of an endovascular approach to DBS, 31 and the ability to chronically record in the superior sagittal sinus superficial to the sensorimotor cortex 22 may lead to the achievement of a minimally invasive BMI.…”
Section: 1922mentioning
confidence: 99%
“…Axon models consisted of 2 μm diameter fibers with compartments representing nodes of Ranvier, myelin attachment segments, paranode main segments, and internode segments connected through an axial resistance [16]. Axonal membrane compartments were each driven using the extracellular mechanism in NEURON (e_extracellular) [6], [8], [43]. We applied a waveform with a 90 μs cathode-leading phase, 400 μs interphase delay, 3 ms charge-balanced anodic phase, and 135 Hz pulse rate [44].…”
Section: Methodsmentioning
confidence: 99%